Sunlight-assisted, biocatalytic formate synthesis from CO2 and water using silicon-based photoelectrochemical cells. Issue 62 (14th July 2016) - Son, Eun Jin; Ko, Jong Wan; Kuk, Su Keun; Choe, Hyunjun; Lee, Sumi; Kim, Jae Hong; Nam, Dong Heon; Ryu, Gyeong Min; Kim, Yong Hwan; Park, Chan Beum
Abstract : A silicon-based photoelectrochemical cell is developed to convert CO2 to formate with water as an electron donor by using formate dehydrogenase from Thiobacillus sp. Abstract : We report on a silicon-based photoelectrochemical cell that integrates a formate dehydrogenase from Thiobacillus sp. (TsFDH) to convert CO2 to formate using water as an electron donor under visible light irradiation and an applied bias. Our current study suggests that the deliberate integration of biocatalysis to a light-harvesting platform could provide an opportunity to synthesize valuable chemicals with the use of earth-abundant materials and sustainable resources.